Cross Section Measurements on Isotopes of Ge and Hf Using the Activation Technique - Galanopoulos, S.; Serris, M.; Perdikakis, G.; Kokkoris, M.; Papadopoulos, C. T.; Vlastou, R.; Lagoyannis, A.; Spyrou, A.; Kalyva, Y.; Harissopulos, S.; Zarkadas, Ch.; Kossionides, S. (HNPS Advances in Nuclear Physics, 2019)
Cross section measurements of neutron induced reactions on isotopes of Ge and Hf have been determined at energies 8.8, 9.6, 10.6, 11.1, 11.4 MeV using the activation technique. Neutrons produced by the 2H(d,n)3He reaction were used to irradiate pellets of natural Ge and Hf02- The neutron flux at the target position was determined using the 27Al(n,a)24Na, 93Nb(n,2n)92mNb and 197Au(n,2n)196Au reference reactions. HPGe detectors of relative efficiency εΓ=80% and 55% were used to determine the decay of the produced unstable nuclei. The cross section values were compared with those taken from the literature.